An evaluation of the impacts of urbanisation on Klip River Wetlands degradation, Johannesburg South - Mabale, Katlego Lennon (My University, 2025)
Wetlands are among the most productive and vulnerable ecosystems in the world, serving fundamental ecological functions such as water purification and water supply. They are however deteriorating due to urbanisation-induced factors. Urbanisation which is increasing as people are consistently moving from rural to urban areas for better economic opportunities, has been linked with high rates of anthropogenic activities in urban areas, which interact with natural ecosystems, thus putting pressure on wetlands. This study, therefore, evaluated the impacts of urbanisation on Klip River Wetland (KRW), by linking water quality in the wetland and the socioeconomic dynamics within two communities in the city of Johannesburg municipality, i.e. Protea Glen (PG) and Lenasia (LENZ). Water samples were collected seasonally, during wet and dry seasons, at four monitoring sites, to assess the spatial and temporal dynamics in the wetland's physicochemical and biological characteristics. This was done by, employing Multi-parameter, Spectrophotometer, Ion Chromatography (IC), Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), and Colilert-18, for assessing the physical, chemical, and biological constituents of the water. The water quality assessment was augmented with community perceptions and attitudes on how urbanisation impact local communities (via closed and open-ended questions), as well as evaluating water degradation factors through field observations and key factors from the open-ended responses. Findings indicated that water degradation is occurring during both wet and dry seasons in the KRW and that there are spatial variations in water quality in the monitored areas of the wetland. Ranking in quality from marginal to poor water quality (S3>S1>S2>S4), with sampling site S4 ranking lowest. Results confirms that KRW quality is influenced by parameters such as pH, turbidity, dissolved oxygen (DO), chemical oxygen demand (COD), nitrate (NO3-), magnesium (Mg2+), calcium (Ca2+), manganese (Mn2+), Escherichia coli (E. coli) and total coliforms, which recorded values that did not comply with the South African Water Quality Guidelines (SAWQGs) and the Klip River Catchment’s (KRCs) In-stream Water Quality Guidelines (ISWQGs). The close-ended sociodemographic characteristics of the surveyed community revealed that there were more males (52%) than females (48%), and that there is a relationship between gender and other sociodemographic characteristics such as age, education background, and economic v status. According to the respondents, the most significant influences of urbanisation on KRW include infrastructure (25%), environment degradation (22%), economic activities (19%), and waste disposal (17%), within the communities. These results, together with field observations, linked factors related to urbanisation within the communities that interact with water quality such as traffic congestion, drainage and sewage issues, construction activities, wildfires, mining and industrial activities, and waste. The convergence of these socioeconomic findings, with the water quality assessment, substantiates water quality degradation within the KRW, linked to urbanisation. These findings underscore the urgent need for integrated urban planning, water resource management and conservation strategies to mitigate the adverse effects of urbanisation on KRW.
Thesis (M.Sc. (Geography and Environmental Science)) -- University of Limpopo, 2025
Keywords: Urbanisation; Klip River Wetland; socioeconomic dynamics; water quality; Environmental degradation; Water-supply; Wetlands management; Wetlands ecology; Urbanization -- South Africa -- Gauteng